Hypertension and arterial wall stiffness in clinical practice: literature review - L. I. Gapon (Российский кардиологический журнал)
Arterial stiffness, as a marker of subclinical target organ damage in patients with hypertension (HTN), is an important and independent predictor of mortality and cardiovascular morbidity. The review examines factors contributing to increased vascular wall stiffness with a focus on smoking, pathogenesis of increased arterial stiffness with aging, and the effect of arterial stiffness on increased systolic and pulse pressure. Particular attention is paid to the effect of pulse pressure on the risk of cardiovascular events, primarily on the incidence of stroke and cognitive impairment. Thiazide-like diuretics and calcium antagonists have the greatest evidence base in HTN treatment in the elderly due to their ability to reduce systolic and pulse pressure, reduce arterial stiffness and have a positive effect on prognosis. The use of amlodipine/indapamide retard combination promotes more effective treatment of elderly patients with HTN.